The Effect of Urbanization on The Stand Structure of A Mangrove Forest in Likas Bay, Sabah Malaysia - Andy R. Mojiol (HUTAN TROPIKA, 2023)
The aims of this study were to determine the effect of urbanization on species composition, change to stand structure and tree species on the mangrove stand between the housing development and the river. Two (2) plots were established, with five (5) subplots each measuring 10m x 10m. Simpson’s Index, Shannon-Weiner Index, Shannon evenness and Important Value Index (IVI) were used to determine the diversity and abundance of tree species. There are 4 species found in both plots which are Avicennia alba, Avicennia marina, Rhizophora mucronata and Rhizophora apiculata. The most abundant species is the R. apiculata with an IVI of 86.99 percent (%). The Simpson’s Index value calculated for the forest was 0.75, while the value for the Shannon-Weiner (H’) was 1.38. This indicates the area has low diversity in mangrove trees. The Shannon evenness (E) was 0.99. This means the area is completely covered in standing trees. In this study, the stand structure was measured using tree Diameter at Breast Height (DBH), height and crown size. The data indicates that mangrove trees approaching the housing developments experienced a steady decrease in DBH, height, and crown size. Trees in the middle of the forest had the largest DBH and height. The DBH and height of trees approaching the river steadily decreased but had larger crowns compared to the other subplots. Whereas, water quality and the presence of sediments were two other additional aspects used to measure the impact of housing developments on mangrove forests. Urbanization projects do not leave any noticeable impact on the clearness of water in mangrove forests, but does for sediments. As a conclusion, urbanization project such as housing development do leave an impact on mangrove forests in the Likas bay, Malaysia. More future studies will shed more light on how housing developments impact mangrove forests